The Effect of Service Quality and Product Quality on User Satisfaction with the Mekari Qontak Application in the Public Relations Division of the Politeknik Negeri Jakarta - Ikko Septiana; Ridho Riadi Akbar (Dinasti International Journal of Digital Business Management, 2025)
Digital transformation requires higher education institutions to adopt information technology to improve the quality of communication services. The Public Relations Division of the Politeknik Negeri Jakarta has implemented the Mekari Qontak application as a Customer Relationship Management (CRM) platform. However, issues with application stability and consistency of technical support have been identified, which could potentially affect user satisfaction. This study aims to examine the partial and simultaneous effects of product quality and service quality on user satisfaction with Mekari Qontak application in this environment. The research methodology uses a quantitative approach with a causal associative study design. Data were collected through a Likert scale questionnaire from 86 respondents selected using simple random sampling. The analysis techniques used include descriptive analysis and multiple linear regression verification. The research findings show that product and service quality have a positive effect on user satisfaction in the strong category. Service quality contributes significantly through the aspects of reliability and responsiveness, while product quality excels in performance and feature completeness. Both variables are proven to strongly influence user satisfaction. This study provides strategic recommendations for managers to improve system stability and serves as an academic reference related to CRM management in educational institutions.